Immuno-oncology for renal cell carcinoma treatment: future perspectives for combinations and sequences with molecularly targeted agents. (1st February 2017) - Porta, Camillo; Toscani, Ilaria; Czarnecka, Anna M.; Szczylik, Cezary A.
ABSTRACT: Introduction: From a theoretical viewpoint, combining molecularly targeted agents endowed with antiangiogenic properties with immunotherapy makes sense in treatment of metastatic renal cell carcinoma (RCC); this neoplasm is highly angiogenesis-dependent, as well as potentially immunogenic. Areas covered: The authors performed a literature search looking for clinical trials aimed at evaluating efficacy and tolerability of combinations (or sequences) of molecularly targeted agents and different immunotherapeutic approaches in metastatic RCC. Expert opinion: Combinations of molecularly targeted agents with old immunotherapeutics (i.e., cytokines) seem to add little to the presently available treatment standards (mainly monotherapy with targeted agents). Newer combinations with immune checkpoint inhibitors are promising but cumulative toxicity is an important issue, although highly dependent on the different companion drugs. Combinations with vaccines are ongoing, but first available data are not encouraging. A more thorough comprehension of the complex effects of these combinations on the immune system is mandatory to develop less empiric treatments.